2003
DOI: 10.1051/apido:2003018
|View full text |Cite
|
Sign up to set email alerts
|

Oxytetracycline hydrochloride activity in honey bee larvae (Apis mellifera) following medication with various doses

Abstract: -Four replicated experiments were conducted to determine the concentration of oxytetracycline hydrochloride (OTC) in honey bee (Apis mellifera) larvae following application of the antibiotic to honey bee colonies. In the first experiment, the mean OTC concentration was significantly greater in whole larvae than in larval guts sampled from hives on the day immediately following treatment. In two further experiments, 0.3 g, 0.5 g and 1.0 g active OTC in caster sugar was administered to single-and double-storey c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…All the large larvae in unsealed cells became radioactive within 48 hours. McKee et al (2003) confirmed that OTC treatment reaches larvae rapidly : on the day following a treatment with 0.3 to 1 g of OTC, they measured in larvae an OTC level ranging between 13.3 and 172.2 mg.kg -1 .…”
Section: Tetracycline Residues In Hivesmentioning
confidence: 67%
“…All the large larvae in unsealed cells became radioactive within 48 hours. McKee et al (2003) confirmed that OTC treatment reaches larvae rapidly : on the day following a treatment with 0.3 to 1 g of OTC, they measured in larvae an OTC level ranging between 13.3 and 172.2 mg.kg -1 .…”
Section: Tetracycline Residues In Hivesmentioning
confidence: 67%
“…Oxytetracycline is used in the control of European foulbrood, a disease of honeybees caused by Melissococcus plutonius . The antibiotic is applied mixed with sugar or water and reaches minimal inhibitory concentrations in the larval guts within 24 h post treatment, but declines rapidly to a level under MIC within two to five days [7, 8]. In the USA, bees have been exposed to prophylactic oxytetracycline use for over 50 years and high levels of tetracycline resistance can be detected in bee guts [6].…”
Section: Introductionmentioning
confidence: 99%
“…After six days of in vitro rearing, larvae treated with 100 μg/mL OTC were calculated to receive a total dose of 105–120 μg/g OTC per larvae, not accounting for the 34-h half-life of OTC in water 28 . Accordingly, the dose of OTC per larva in vitro is ~ 10× the quantity of OTC previously reported in honey bee larvae from a field colony treated with 300 mg OTC 39 . In the field, we anticipate that concentrations lower than 100 μg/mL will be sufficient due to the presence of social immunity within a colony as a mechanism for pathogen defense.…”
Section: Resultsmentioning
confidence: 84%
“…In fact, the concentration of OTC required to inhibit this strain in vitro is higher than the expected accumulation of the antibiotic during a standard treatment. For example, honey bee larvae sampled from one or two chamber field colonies, one day after colony treatment with 300 mg OTC (in excess of current label recommendations of 200 mg), were shown to have OTC concentrations of ~ 13 and 9 μg/g, respectively 39 . While this appears to be a sub-therapeutic dose for infection with M. plutonius 2019BC1, social immunity (see below) may influence on colony-level antibiotic efficacy.…”
Section: Resultsmentioning
confidence: 99%